The Online Sales Application Of Black And White Print Based On Yii Framework On Higher Education E-Commerce Website - Mardiana, Mardiana; Lutfiani, Ninda; Saga, Rivialdo Sultan (Pandawan, 2019)
Raharja Internet Cafe as a facility in Raharja College which is provided for Personal Raharja in helping provide the need for lecture activities. Raharja Internet Cafe has a problem that the system of selling black and white print products that apply consumers must come directly to the RIC room at LV-002 at Raharja College, but Raharja Internet Cafe cannot accommodate many consumers because of the limited area. These problems are the background for the establishment of an electronic sales system (e-commerce) based on Yii framework with the aim of facilitating the sale of black and white print products for consumers and staff of Raharja Internet Cafe. E-commerce website at Raharja Internet Cafe is a web-based application with a structured programming concept. The e-commerce application development Shop Copy Nicky uses 4 (four) stages according to the steps that exist in software development, including the stages of observation, analysis, literature study consisting of 10 (ten) literature and implementation. The conclusion of the e-commerce website development on Raharja Internet Cafe is that the website built can make it easy for consumers to make transactions, and Raharja Internet Cafe can get comprehensive and real time reports about sales data, and payment systems for consumers that are easier because they use payment system that is done online